Quasi-static Compressive Properties and Behavior of Single-cell Miura Origami Column Fabricated by 3D Printed PLA Material - Triawan, Farid; Denatra, Geraldy; Djamari, Djati (http://dx.doi.org/10.31427/IJSTT.2020.3.2.5, 2020)
The study of a thin-walled column structure has gained much attention due to its potential in many engineering applications, such as the crash box of a car. A thin-walled square column usually exhibits high initial peak force, which may become very dangerous to the driver or passenger. To address this issue, introducing some shape patterns, e.g., origami folding pattern, to the column may become a solution. The present work investigates the compressive properties and behavior of a square box column structure which adopts the Miura origami folding pattern. Several test pieces of single-cell Miura origami column with varying folding angle and layer height are fabricated by a 3D printer. The filament is made of Polylactic Acid (PLA), which is a brittle material. Then, compression tests are carried out to understand its compressive mechanical properties and behavior. The results show that introducing a Miura origami pattern to form a thin-walled square column can dramatically lower down the initial peak stress by 96.82% and, at the same time, increase its ductility, which eventually improves the energy absorption capacity by 61.68% despite the brittle fracture behavior.